2018
DOI: 10.1111/joes.12266
|View full text |Cite
|
Sign up to set email alerts
|

The Drivers of Structural Change

Abstract: The main goal of this paper is to provide an integrated survey of the literature devoted to identifying the drivers of structural change, broadly defined as the process of reallocation of economic activity across the three broad sectors agriculture, manufacturing and services. Using the GGDC 10‐Sector Database, this paper first presents the empirical facts associated with structural change in different regions of the world – that is Europe and the USA, Asia, Latin America, and Africa – then reviews four determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(41 citation statements)
references
References 256 publications
(393 reference statements)
5
34
0
2
Order By: Relevance
“…The distribution of the labour force and the economic structure by sectors indicate the economic development level of countries. Differences between the employment and value added shares reflect cross-sector differences in labour productivity (Van Neuss, 2019). The speed and scope of the sectoral shifts reflect the willingness and ability of labour and capital to address the high productivity sectors and all these factors affected by the policy and institutional environment (ESCAP, 2016).…”
Section: Economic Growth and Sectoral Composition Of Turkish Gdpmentioning
confidence: 99%
“…The distribution of the labour force and the economic structure by sectors indicate the economic development level of countries. Differences between the employment and value added shares reflect cross-sector differences in labour productivity (Van Neuss, 2019). The speed and scope of the sectoral shifts reflect the willingness and ability of labour and capital to address the high productivity sectors and all these factors affected by the policy and institutional environment (ESCAP, 2016).…”
Section: Economic Growth and Sectoral Composition Of Turkish Gdpmentioning
confidence: 99%
“…In contrast, studies like Baumol [1967]; Echevarria [1997]; Kongsamut et al [2001]; Laitner [2000]; Matsuyama [1992] construct a range of models that explain structural change without relying on balanced growth. There is also now a considerable literature on the empirical divers of structural change [Van Neuss, 2019].…”
Section: Theories Of Growth Development and Structural Changementioning
confidence: 99%
“…Endogenous growth theories include human capital development, knowledge spillovers as well as research and development (Aghion & Howitt, 1992;Grossman & Helpman, 1991a, b;Romer, 1990). Lucas and Romer included spillover effects based on Arrow (1962) and Uzawa (1965), who observed that learning-by-doing and knowledge spillover positively affected labor productivity on the aggregate level of the economy and leading to structural change (Matsuyama, 2008;Ngai & Pissarides, 2007;Swiecki, 2017;van Neuss, 2019). Romer (1986) started with persistent growth explained by the impact of externalities on economic development (Krueger, 1997).…”
Section: Growth Theoriesmentioning
confidence: 99%